Evaluation of the Bactericidal Activity of Gramicidin S Against Streptococcus pneumoniae and Staphylococcus aureus Clinical Isolates with Single and Multiple Exposure - A. V. GUROV; K. E. BOROVKOVA; K. L. KRYSHEN; L. R. NIKIFOROVA; J. V. SALMOVA (Антибиотики и Химиотерапия, 2022)
Background. Sore throat of infectious and inflammatory origin is one of the most common reasons for the prescription of antimicrobial drugs. The use of antimicrobial peptides (AMPs) for topical therapy may be a promising solution, due to the peculiarities of AMPs’ mechanism of action, taking into account the high importance of microbial resistance spread problem in relation to systemic etiotropic drugs.The aim of the study was to assess the formation of resistance to AMP Gramicidin S (GS) of clinical isolates of Streptococcus pneumoniae and Staphylococcus aureus, including strains resistant to antimicrobial drugs during repeated exposure, in the setting close to their actual use in clinical practice.Materials and methods. The object under study is AMP GS. The test microorganisms are reference strains of S.pneumoniae (ATCC 6303), S.aureus (ATCC 6538–P), and 10 strains of clinical isolates of each type of microorganisms, types with antimicrobial resistance (including MRSA). At the first stage, the antimicrobial activity of GS was evaluated by the method of microdilutions in plates by estimating the value of the minimum inhibitory and the minimum bactericidal concentrations (MIC and MBC, respectively). At the second stage, using reference strains and 4 clinical isolates of each microorganism, including types with antimicrobial resistance, resistance was formed in two ways simultaneously (with liquid and solid media) for 7 consecutive passages over 7 days with GS at concentrations equal to 0.5 and 1.0 MIC. The number of surviving microorganisms was estimated and the MIC and MBC were determined at each passage.Results. At the first stage, the MIC of GS in relation to S.pneumoniae was 8 µg/ml for 5 strains, 16 µg/ml for 5 strains, and 4 µg/ml for one. For 10 out of 11 strains of S.aureus, including MRSA, the MIC of GS was 4 µg/ml (for 1 strain — 8 µg/ml). For 4 strains of S.pneumoniae, MBC of GS was equal to MIC (16 µg/ml), for 7 strains MBC was 4–8 times higher than MIC, and mostly amounted to 32 µg/ml (for 1 strain — 64 µg/ml). MBC for 6 strains of S.aureus was equal to MIC (4 µg/ml), for the 5 remaining strains MBC was 2–8 times higher than MIC, but did not exceed 64 µg/ml. At the second stage, it was found that the estimated values of GS MIC and MBC with repeated exposure to GS remained at the same level for 7 passages in all strains, including those resistant to antibiotics in liquid and solid media.Conclusions. Gramicidin S demonstrated high bactericidal activity against reference strains and clinical isolates of leading pathogenic microorganisms S.pneumoniae and S.aureus, including strains resistant to systemic antimicrobial drugs, while MIC and MBC did not exceed concentrations contained in single doses of drugs used in clinical practice. During repeated exposure (7 passages in 7 days), there were no signs of the formation of resistance of test strains of pathogens, including those resistant to systemic antimicrobial medicines from the groups of beta-lactams, macrolides, fluoroquinolones, tetracyclines, aminoglycosides, etc.